ROLE OF NURSE IN FOSTERING AWARENESS ON THE HIDDEN EPIDEMIC-RECOGNIZING AND ADDRESSING DOMESTIC VIOLENCE AND ABUSE - Santhosh Kumar. J, Dona Jose, Febin Mathew, Dr. Jomon Thomas, Amrita Singh, Sam Jose, Arun James, (EPRA International Journal of Research and Development (IJRD), 2023)
Domestic violence and abuse are pervasive issues that affect individuals across diverse demographics, impacting mental health, maternal well-being, and community safety. Nurses, as frontline healthcare professionals, play a pivotal role in recognizing and addressing these issues. This article explores the multifaceted role of nurses in fostering awareness about domestic violence and abuse. It emphasizes the importance of early identification, supportive care, and referral to appropriate resources. By addressing these challenges, nurses contribute significantly to enhancing mental health, ensuring maternal well-being, and promoting community safety.